Enhanced effect and mechanism of colloidal nano-SiO2 modified rubber concrete. (16th May 2023) - Xu, Yaoqun; Wang, Juan; Zhang, Peng; Guo, Jinjun; Hu, Shaowei
Graphical abstract: Highlights: The gray value correction method of the energy dispersive spectrometer map quantified the element distribution of the rubber-cement interfacial transition zone (ITZ). The highest relative enhancements (30.3%) in early rubber concrete compressive strength were achieved by adding colloidal nano-SiO2 (CNS). The microcracks width at the ITZ of rubber concrete decreases from 35 ∼ 45 µm to 3 ∼ 10 µm in CNS-modified rubber concrete. Compared with rubber concrete, the length of the growth segment with element distribution in the CNS-modified rubber-cement ITZ decreased by more than 40%. Abstract: With the addition of rubber particles, the intensity of concrete reduces, limiting the application of rubber concrete in engineering. To increase the strength and applicability of rubber concrete, a highly dispersible colloidal nano-SiO2 (CNS) is used as an admixture. This study analyzes the enhanced effects and mechanisms of CNS on rubber concrete. The microcracks measurement results indicated that the width of the microcracks in the CNS-modified rubber concrete ranges within 3–10 μm, whereas that in ordinary rubber concrete ranges within 35–45 μm. The gray value correction method of the energy dispersive spectrometer map quantified the element distribution of the rubber-cement interfacial transition zone (ITZ). The results show that, compared with rubber concrete, the length of the growth segment with element distribution in the CNS-modified rubber-cement ITZ decreased by more than 40%. Additionally, the highest relative enhancements (30.3%) in early rubber concrete compressive strength were achieved by adding CNS. These findings indicate that the enhancement mechanism of CNS to rubber concrete can be attributed to the interfacial microstructure modification caused by the surface effect of nano-SiO2 and filling effect of the nanoparticles in the ITZ.